2023
DOI: 10.3390/microorganisms11020361
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and Endocrine Diseases

Abstract: Viral infections have been frequently associated with physiological and pathological changes in the endocrine system for many years. The numerous early and late endocrine complications reported during the current pandemic of coronavirus disease 2019 (COVID-19) reinforce the relevance of improving our understanding of the impact of viral infections on the endocrine system. Several viruses have been shown to infect endocrine cells and induce endocrine system disturbances through the direct damage of these cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 176 publications
0
1
0
Order By: Relevance
“…Prior studies found reduced GH secretion in both acute and post‐acute COVID‐19 patients. 11 , 12 We recently discovered that subjects with neurologic PASC symptoms at least 6 months after initial infection had reduced average groupwise GH secretion compared with individuals who recovered from COVID–19 without lingering symptoms. 13 The neurologic PASC symptoms of fatigue and brain fog coupled with reduced GH secretion mirror the symptom etiology seen in BIAFAC patients following TBI who have profound improvement in neurologic symptoms with GH treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies found reduced GH secretion in both acute and post‐acute COVID‐19 patients. 11 , 12 We recently discovered that subjects with neurologic PASC symptoms at least 6 months after initial infection had reduced average groupwise GH secretion compared with individuals who recovered from COVID–19 without lingering symptoms. 13 The neurologic PASC symptoms of fatigue and brain fog coupled with reduced GH secretion mirror the symptom etiology seen in BIAFAC patients following TBI who have profound improvement in neurologic symptoms with GH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…COVID‐19 is associated with metabolic and hormonal disturbance to multiple organs and systems. 8 , 9 , 10 Altered pituitary function, including reduced plasma growth hormone (GH) has been observed in acute 11 and post‐acute periods. 12 We recently discovered that reduced GH secretion persisted in individuals with neurologic PASC symptoms more than 6 months after initial infection.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus (SARS-CoV) and SARS-CoV-2 belong to the coronavirus family [42]. The principal receptor for SARS-CoV-2, ACE2, manifests a ubiquitous expression across the cellular landscape of endocrine organs, notably prominent in the pancreatic and thyroid tissues [43,44].…”
Section: Covid-19 and Hypothalamic-pituitary Diseasesmentioning
confidence: 99%
“…Several viruses, including Enteroviruses, Herpes Simplex virus, and Varicella-Zoster virus, have been associated with hypophysitis [42].…”
Section: Pathophysiology Of Hypopituitarismmentioning
confidence: 99%
“…In most of the organs, SARS‐CoV‐2 infection results in destabilisation of the host cellular immune response and release of proinflammatory cytokines, dysregulated production of inflammatory cells, endothelial dysfunction, and coagulation abnormalities (Table 1). 20–43 It has been long known that upon infection, host cells produce miRNAs to counter viral attacks by regulating the host‐immune response 44,45 . Moreover, viruses also transcribe miRNAs that may interfere with the host‐cellular defence system 45 .…”
Section: Introductionmentioning
confidence: 99%